Redes sociais e a inteligência no sistema de segurança do poder judiciário - Seabra, Marcelo Canizares Schettini (2019)
This Paper’s objective was, based on the characteristics of the existing intelligence services of the Intelligence System of the Judiciary, to search for evidence and congruences between the functionality of the intelligence activity of the Court's security unit and the concept of Policy Network Management. To Achieve said objective this paper was divided in three parts: The first one is a revision of the literature around this theme, showing intelligence actions from remote times all the way to actuality. Thus, this section was focused on analysing existing documents of the Judiciary, being possible to determine which normatives specifically deal with this matter is the Justice system. The second part is based on the report entitled, by the National Security Council, Diagnostic of the Judiciary’s Institutional Security. The data and results gathered on this report were analyzed to identify, in the interactions of the Court’s Intelligence Unit, characteristics of Policy network on the Public Administration. It was possible to find congener relations between the Judiciary intelligence and the networks. Lastly, aiming to pair the most characteristics possible in the relation “intelligence x network”, it was elaborated a questionnaire with 11 questions, ad sent to 35 Courts, allowing, this way. Lastly, aiming to match the greatest number of possible characteristics of the intelligence-tonetworks relationship, a questionnaire with 11 interrogatives was sent to 35 courts, thus allowing evidence that intelligence activities carried out by Judiciary’s security, correspond to the networked organizational configuration